2021
DOI: 10.21203/rs.3.rs-898920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immersive Virtual Reality Improves Labor and Delivery Experience for Women: A Randomized Controlled Trial

Abstract: Objective: To evaluate the effectiveness of immersive Virtual Reality (VR) in laboring women on patient satisfaction as a distractive tool and pain relief.Methods: Randomized, controlled clinical trial with 42 laboring women allocated to VR intervention and control groups. Among the VR group, patient satisfaction with the use of VR was assessed by a Virtual Reality Satisfaction Survey and questioning whether they would choose VR in future labor. As a primary outcome patient satisfaction scores regarding the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
2
6
0
2
Order By: Relevance
“…It has demonstrated benefits in both acute (e.g., procedure-related) and chronic pain ( 4 , 5 ). We and others have previously demonstrated the effectiveness of VR in reducing pain in persons in labor ( 6 9 ). Our study was unique in that – unlike others – our visualization was specifically targeted towards laboring persons.…”
Section: Introductionmentioning
confidence: 91%
“…It has demonstrated benefits in both acute (e.g., procedure-related) and chronic pain ( 4 , 5 ). We and others have previously demonstrated the effectiveness of VR in reducing pain in persons in labor ( 6 9 ). Our study was unique in that – unlike others – our visualization was specifically targeted towards laboring persons.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, the demonstration to 50 parturient women of ultrasound images of their children via VR glasses decreased the pain scores under cervical dilatation by 9 cm; reduced anxiety scores and improved the perception of therapeutic support (Akin et al, 2021). Parturient women subject to VR immersion had lower pain scores and higher satisfaction with the childbirth experience (Carus et al, 2022). A systematic review of eight randomized control studies with a total of 466 patients showed that VR performs well in pain relief, anxiety reduction, and increasing satisfaction during natural childbirth .…”
Section: дискусіяmentioning
confidence: 96%
“…Так, демонстрація 50 породіллям ультразвукового зображення власної дитини за допомогою ВР-окулярів суттєво зменшила оцінки болю при розкритті шийки на 9 см; знизила показники тривоги та покращила сприйняття терапевтичної підтримки (Akin et al, 2021). Породіллі, що отримували імерсійну ВР, мали нижчі показники болю та вищу задоволеність досвідом пологів (Carus et al, 2022). Системний огляд восьми рандомізованих контрольних досліджень із загальною кількістю 466 пацієнток показав, що ВР -ефективний метод знеболювання, зниження занепокоєння та підвищення задоволеності під час природних пологів .…”
Section: дискусіяunclassified
“…The picture above shows the changes in anxiety experienced by mothers before and after doing pregnancy exercises and hypnosis techniques (Carus, Albayrak, Bildirici, & Ozmen, 2022). Previously there were 6 people who experienced severe anxiety, after receiving education and demonstration there was a change in the level of anxiety, namely the severe category to 1 person, moderate anxiety 2 people, mild anxiety 4 people, and the remaining 5 people were in the normal category.…”
Section: Distribution Of Psychological Disorders With Anxiety Before ...mentioning
confidence: 99%